PENGARUH PERUBAHAN SUDUT PENGAPIAN TERHADAP GAS BUANG MOTOR 4 LANGKAH - Badrawada, I Gusti Gde (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
The aim of this research is to find the influence of ignition timing to emission of 4 stroke motorcycle. The emission is affected by several things such as octane number, combustion process, air consumed. Emission will affect to the green house gas and finally will produce global warming. In addition, the available of fuel will decrease year after year so we must use it effectively. To know the influence of ignition timing to emission, then, this research was done by experimental method to find data. The timing ignition was chosen in 10o, 15oand 20o. For each timing ignition the engine would be rotated from 3000 rpm to 6000 rpm, then the data of emission would be measured by measurement apparatus. From this research, it could be found that ignition timing in 10o had combustion process better relatively than others. It was proven by emission produced by this timing ignition’s combustion process.